Penggunaan model problem based learning (PBL) untuk meningkatkan pemahaman konsep IPA siswa kelas V sekolah dasar - Fitria Ramadhan; Muhammad Rizal Fauzi; Susilawati Susilawati (IKIP Siliwangi, 2024)
This research has several objectives, including to find out; (1) the increase in the application of the Problem Based Learning model to student learning activities; (2) the process of applying the Problem Based Learning model in improving students' concept understanding abilities; and (3) the obstacles faced by teachers and students in implementing learning by using the Problem Based Learning model. The method used is mix method with sequential explanatory design. The research was located at SD Negeri Cigugur Tengah Mandiri 1 with 30 fifth grade students as the research subjects. Data collection techniques through tests (pretest and posttest), observation sheets, interviews and questionnaires. Based on quantitative data obtained through the N-gain test, there is an increase in the concept understanding ability of fifth grade students with an N-gain score of 0.73 categorized as high. While the qualitative data results of the acquisition of student response questionnaire scores obtained an average value of 85% in the “Very Good” category and the teacher's questionnaire gave a positive response. The obstacles faced by students include difficulties in understanding the concept of material changes in the form of objects, students are less actively involved in working in groups so that the material presented is not well absorbed by students, lack of self-confidence so that students are embarrassed to be active in asking questions and presenting the results that have been obtained. The obstacles faced by teachers from the results of interviews reveal that the level of students' ability to understand the material is different, lack of concentration, less active in learning and lack of props because it must require extra time and sufficient costs.